Development of the ‘Tangga Kesantunan’ Board Game as a Civic Education Learning Medium to Instill Politeness Values in Third-Grade Elementary School Students - Triya Abida Kolis; Fienna Saadatul Ummah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The decline in polite behavior in elementary school students is one of the problems that needs attention in PPKn learning. This study aims to develop the board game media "Tangga Kesantunan", to determine the level of feasibility, practicality, and effectiveness of the media as a means of instilling polite values in grade III students of SDN Rancang Kencono II Lamongan. This study uses the Research and Development (RD) method with the ADDIE development model consisting of the Analyze, Design, Development, Implementation, and Evaluate stages. Data collection techniques were carried out through interviews, observations, student and teacher response questionnaires, and media expert validation. The research instruments included expert validation sheets, student and teacher response questionnaires, and student polite behavior observation sheets. The results showed that the board game media "Tangga Kesantunan" obtained a media expert validation percentage of 98% with a very feasible category. The results of student responses obtained a percentage of 85.8% and teacher responses of 89.33% with a very practical category. In addition, the results of observations after the application of the media showed an average percentage of 88.4% with a very effective category. Based on these results, the "Tangga Kesantunan" board game was deemed feasible, practical, and effective as a learning tool for Civics (PPKn) to instill the value of politeness in third-grade elementary school students.